Jewish education and formation in Glasgow: a case study - McKinney, Stephen J. (Journal of beliefs and values, 2004)
This article explores the formational provision within a faith community when faith schooling ends at the primary stage. A case study, part of a larger multi‐faith study, examined the Jewish community in the greater Glasgow area—a small, and shrinking, community with a long history of relatively peaceful integration but increasingly pressurised by secularisation, assimilation and emigration. There is a well‐attended Jewish primary school, but no secondary school. A range of approaches to youth formation and education for children of secondary age has evolved—approaches linked to a variety of conceptions of Jewish identity. The aim, ultimately, is to include all Jewish children, no matter how they construct their Jewish identity, in the community.